Analysis of convective condensation heat transfer for moist air on a three-dimensional finned tube. (August 2021) - Gu, Yuheng; Ding, Yudong; Liao, Qiang; Fu, Qian; Zhu, Xun; Wang, Hong
Highlights: Experimental study on the condensation heat transfer of moist air was carried out. The enhancement of three-dimensional finned tube was studied. The latent and sensible heat transfer was obtained and analyzed in detail. Semi-theoretical correlations were developed to predict the heat transfer process. Abstract: The condensation of moist air plays an important role in daily life and industry. During the condensation process, single-phase and phase-change heat transfers occur simultaneously. A three-dimensional finned tube is an effective element for enhancing heat transfer. However, the latent and sensible heat transfer during moist air condensation outside a three-dimensional finned tube has not been experimentally studied. In this study, experiments were performed using a three-dimensional finned tube to enhance the moist air condensation process. For a better understanding of the enhancement mechanism, latent and sensible heat transfer variations with relative humidity ranging from 0.75 to 0.95 and Reynolds numbers ranging from 838 to 3444 were obtained and analysed. A smooth tube was used for the comparison. The experimental results indicated that the three-dimensional finned tube was favourable for the enhancement of moist air condensation, especially for latent heat transfer. When the Reynolds number was 2504, the latent and sensible heat transfers of the three-dimensional finned tube were 43.6%–81.8% and 15.6%–22.9% higher than those of the smooth tube, respectively. In addition, the latent and sensible heat transfers of the three-dimensional finned tube and the smooth tube were obtained under different velocities of moist air, and empirical correlations were developed to predict the sensible and latent heat transfers with deviations of less than ± 20%. The results obtained can provide a reference for the design of three-dimensional finned tubes used in moist air condensation.